Call to Teach : Philosophy, Process, and Pragmatics of Social Work Education. - Fox, Raymond (Council on Social Work Education, 2013)
"Teaching is the substantive business of academe. It is often viewed, however, as an expectable given, a routine function, an intrusion to be tolerated rather than an attribute to be cultivated," states author Raymond Fox in the Preface to The Call to Teach. In this book Fox looks at teaching from the opposite perspective, approaching the task as something to value, respect, and appreciate as a professional activity and a scholarly endeavor. It concentrates on helping social work educators develop practical strategies, boost confidence, create artful and imaginative presentations, and use a variety of approaches adapted to specific situations. Overarching themes include the pivotal place of competence building; the intersection of science and art; evidence-based practice and experiential wisdom in advancing effective instruction; the pertinence and application of lesson planning and design; and adult learning processes and learning styles. Drawing from his many years of professional experience, Fox encourages readers to use both the logical left and the artistic right halves of the brain to convey social work knowledge, values, and skills and aid students in their journey from conceptual knowledge to competent doing in their professional careers. Raymond Fox, PhD, LCSW, teaches at Fordham University, where he has led a number of advanced master's and doctoral level courses in areas such as individual and family treatment, professional development, and the philosophy of science, as well as social work education and practice. His workshops for Fordham faculty members on teaching methodology and curriculum development are frequently presented to other university faculties. The author of many professional journal articles and book chapters, Dr. Fox also has published three books. He holds a BA from City University of New York (Queens); an MSW from Fordham University; and an MPA and PhD from New York University